Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1038/383621a0
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for generation of long-range synchronous fast oscillations in the cortex

Abstract: Synchronous neuronal oscillations in the 30-70 Hz range, known as gamma oscillations, occur in the cortex of many species. This synchronization can occur over large distances, and in some cases over multiple cortical areas and in both hemispheres; it has been proposed to underlie the binding of several features into a single perceptual entity. The mechanism by which coherent oscillations are generated remains unclear, because they often show zero or near-zero phase lags over long distances, whereas much greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
448
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 640 publications
(482 citation statements)
references
References 26 publications
28
448
3
Order By: Relevance
“…Gamma range (30 to 50 Hz) neural synchronization may be a key mechanism of information processing in neural networks, underlying the binding of both sensory and temporal features of objects. Furthermore gamma range synchronization is thought to depend on the glutamatergically mediated interplay between excitatory projection neurons and GABAergic circuits (see Traub et al 1996), which we have postulated to be abnormal. We thus have obtained preliminary data on synchronization in response to auditory input (McCarley et al, in press).…”
Section: Gamma Frequency Band Abnormalities In Schizophreniamentioning
confidence: 96%
“…Gamma range (30 to 50 Hz) neural synchronization may be a key mechanism of information processing in neural networks, underlying the binding of both sensory and temporal features of objects. Furthermore gamma range synchronization is thought to depend on the glutamatergically mediated interplay between excitatory projection neurons and GABAergic circuits (see Traub et al 1996), which we have postulated to be abnormal. We thus have obtained preliminary data on synchronization in response to auditory input (McCarley et al, in press).…”
Section: Gamma Frequency Band Abnormalities In Schizophreniamentioning
confidence: 96%
“…12 Dominant patterns in cortical networks comprise theta-(4 to 12 Hz), beta-(13 to 30 Hz) and gamma-(B30 to 100 Hz) frequency oscillations, which synchronize the action potential generation ('spiking') of principal cells with great precision, sometimes over large distances of corticocortical connections. 10,[13][14][15] Importantly, inhibitory interneurons have a key role in organizing these highly coordinated patterns of activity. In cortical networks, inhibition is mainly mediated by neurotransmitter, g-aminobutyric acid (GABA), and research during the past decade has revealed an astonishing heterogeneity of GABAergic interneurons at the molecular, morphologic and functional level.…”
Section: Introductionmentioning
confidence: 99%
“…The same currents are largely responsible for local field potentials and EEG. The firing is grouped in time by oscillations in dendritic current in the beta (12-30 Hz) and gamma (30-80 Hz) ranges that arise from negative feedback among excitatory and inhibitory neurons (Freeman, 1975(Freeman, , 2004; Appendix 2.4 in Part 2) with facilitation by the molecular dynamics of synaptic receptors (Traub et al, 1996;Whittington et al, 2000;Kopell et al, 2000). The synchrony between pairs of EEG records can be measured by any of a variety of methods (Lachaux et al, 1999;Le Van Quyen et al, 2001;Quiroga et al, 2002), including the phase difference of oscillations in which they share the same frequency.…”
Section: Introductionmentioning
confidence: 99%